1982
DOI: 10.1002/jobm.3630220506
|View full text |Cite
|
Sign up to set email alerts
|

Factors regulating the steroid 11-hydroxylation by non-germinating spores ofCunninghamella elegans (LENDNER)

Abstract: In the presence of malate or citrate sporangiospores of C. elegans were able to hydroxylate cortexolone with a rate twofold exceeding that of the control, water suspended spores. Analysis of the intracellular nicotinamide coenzyme pools revealed an increased NADPH:(NADP+ + NADPH) ratio, indicating more effective NADPH-generating systems in malate- or citrate-stimulating spores. Swollen spores remaining in the pregermination state, retained higher cortexolone-hydroxylating activity in the absence of malate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
1989
1989

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…It has been demonstrated that spores are capable of carrying out steroid hydroxylations (Jaworski et al, 1982), including those of A. ochraceus for the lla-hydroxylation of progesterone (Schleg and Knight, 1962;Vezina et al, 1963) and that the use of spores is suitable for large-scale steroid hydroxylation (Singh et al, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that spores are capable of carrying out steroid hydroxylations (Jaworski et al, 1982), including those of A. ochraceus for the lla-hydroxylation of progesterone (Schleg and Knight, 1962;Vezina et al, 1963) and that the use of spores is suitable for large-scale steroid hydroxylation (Singh et al, 1968).…”
Section: Introductionmentioning
confidence: 99%